Experimental evaluation of plastic wake on growing fatigue cracks from the analysis of residual displacement fields. Issue 5 (19th February 2022) - Vasco‐Olmo, Jose M.; Díaz, Francisco A.; Camacho‐Reyes, Alonso; James, Neil; Antunes, Fernando V.
Abstract: A growing fatigue crack gives rise to a plastically deformed wake of material that envelops the crack. In this work, the plastic wake extent during fatigue crack growth is experimentally quantified by analyzing the crack tip displacement fields measured with digital image correlation. A novel technique based on use of a yield criterion is proposed that uses the undamaged state of the specimen as the reference state in the image processing. The plastic wake was identified by differentiation of the residual displacement fields obtained with a near‐zero load level to avoid any rigid body motion. The plastic wake extent was then found by assuming that the boundary between the elastic and plastic regions would occur when the equivalent stress was higher than the yield stress of the material. The results presented can contribute to a better understanding of the mechanisms driving fatigue crack propagation. Highlights: Quantification of the plastic wake by analysing residual displacement fields using DIC. Use of the undamaged state of the specimen as the reference for image processing. Plastic wake area as quantifying parameter for residual fatigue displacements. Application of the von Mises yield criterion to estimate the plastic wake extent.